2022
DOI: 10.18280/ria.360415
|View full text |Cite
|
Sign up to set email alerts
|

Online Transaction Fraud Detection Using Efficient Dimensionality Reduction and Machine Learning Techniques

Abstract: In recent years, there has been a rapid increase in the number of online transactions. Substantial growth has been reported in e-commerce and e-governance in the past few years. Due to this the number of people using online payment methods has also increased. This has led to an exponential rise in the number of transactions that happen every day. This increase in online transactions has further led to an increase in the number of frauds in the transactions. There is an ever-growing need to detect these fraudul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The gradient-boosted trees approach is one of the most used and well-implemented in form of a decision tree. The XGBoost tree structure is shown in Figure 3 [35][36][37].…”
Section: Extreme Gradient Boost Classifiermentioning
confidence: 99%
“…The gradient-boosted trees approach is one of the most used and well-implemented in form of a decision tree. The XGBoost tree structure is shown in Figure 3 [35][36][37].…”
Section: Extreme Gradient Boost Classifiermentioning
confidence: 99%
“…To cope with these matters, now that a number of educational institutions and researchers have begun to pay attention to the application of data-driven methods in education management, it's been found that students' learning needs can be predicted more accurately through the analysis of students' online learning behavior and feedback [9][10][11], and educational resources could be updated and optimized effectively via data analysis and management of knowledge libraries, so as to meet students' personalized learning needs [12][13][14][15][16]. However, existing studies mostly talk about every single analysis and prediction method, and few of them have been concerned about how to effectively combine these methods with knowledge library management.…”
Section: Introductionmentioning
confidence: 99%
“…A New Methodology of Knowledge Point Sequence Generation and Learning Path Recommendation by Knowledge Reasoning information overload, and learners always feel lost in the countless courses and knowledge points [5][6][7][8][9]. Besides, the conventional education mode is always rigescent and fixed, so it's impossible to adapt to the individual needs of learners and adjust the content according to their respective knowledge foundation [10][11][12][13][14][15].…”
mentioning
confidence: 99%